2007
DOI: 10.1016/j.metabol.2006.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor and interleukin 1 decrease RXRα, PPARα, PPARγ, LXRα, and the coactivators SRC-1, PGC-1α, and PGC-1β in liver cells

Abstract: During the acute phase response (APR), cytokines induce marked alterations in lipid metabolism including an increase in serum triglycerides, a decrease in hepatic fatty acid oxidation, a decrease in bile acid synthesis, and a decrease in HDL. Here we demonstrate that TNF and IL-1, but not IL-6, decrease the expression of RXRα, PPARα, PPARγ, LXRα and coactivators PGC-1α, PGC-1β and SRC-1 in Hep3B human hepatoma cells. Additionally, treatment of mice with TNF and IL-1 also decreased RXRα, PPARα, PPARγ, LXRα, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
129
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(142 citation statements)
references
References 45 publications
12
129
1
Order By: Relevance
“…Results similar to ours have been found in liver cells, where TNF-␣ and IL-1 caused a marked decrease in retinoid X receptor ␣, PPAR␣, PPAR␥, LXR␣ and SREBP-1c (97). In the liver of apoE knockout mice and in HepG2 cells, inflammatory stress inhibited PPAR␣ and LXR␣ but increased cholesterol accumulation and SREBP-2 (98).…”
Section: Discussionsupporting
confidence: 89%
“…Results similar to ours have been found in liver cells, where TNF-␣ and IL-1 caused a marked decrease in retinoid X receptor ␣, PPAR␣, PPAR␥, LXR␣ and SREBP-1c (97). In the liver of apoE knockout mice and in HepG2 cells, inflammatory stress inhibited PPAR␣ and LXR␣ but increased cholesterol accumulation and SREBP-2 (98).…”
Section: Discussionsupporting
confidence: 89%
“…Type I and type II interferons, tumor necrosis factor, interleukin-12, energy charge, and low NAD + /NADH or oleate/ palmitate ratios have been shown to repress PGC1α expression, localization or transcriptional activity through a variety of signaling pathways (Alvarez-Guardia et al, 2010;Haghikia et al, 2015;Kauppinen et al, 2013;Kim et al, 2007b;Palomer et al, 2009;Scarpulla, 2011). PGC1α is post-translationally modified by a number of signaling pathways important in T cell biology (Akt, p38-MAPK, AMPK, SIRT1, PRMT1) (Fernandez-Marcos and Auwerx, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that LXR, RXR, insulin, and pro-inflammatory cytokines, such as TNF- and IL-1, can modulate the mRNA levels of SREBP-1c [20,30].…”
Section: It Is Conceivable That the Down-regulation Of Srebp-1c In Admentioning
confidence: 99%